Ultra-thin lithium aluminum alloy strip and preparation method and application thereof
Through stirring and smelting and rapid cooling casting technology, combined with pier coarse, vacuum pressurized welding and cold extrusion processes, the problems of uneven composition of lithium aluminum alloy and pores in the preparation of ultra-thin strips during the smelting and preparation process are solved, and the quality and performance of lithium aluminum alloy are significantly improved.
Patent Information
- Application Number
- CN202411920079.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The prior art is difficult to mix lithium and aluminum evenly during the smelting and preparation process, resulting in uneven composition of lithium aluminum alloys and affecting their performance. Especially when preparing ultra-thin lithium aluminum alloy tapes below 50 μm, there are problems of holes.
The high-purity metal lithium and aluminum were homogenized by stirring and smelting, and then the lithium-aluminum alloy rod was obtained through rapid cooling casting technology, and ultra-thin strips were prepared through processes such as pier thickness, vacuum pressurized welding and cold extrusion.
The emergence of holes during the preparation of ultra-thin lithium-aluminum alloy strips is effectively avoided, the quality and performance of lithium-aluminum alloys are ensured, and the preparation of high-end ultra-thin alloy strips below 50μm is achieved.
Smart Images

Figure CN119351807B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium aluminum alloys, and in particular to an ultra-thin lithium aluminum alloy strip and a preparation method and application thereof. Background Art
[0002] Lithium metal, with its excellent theoretical specific capacity (up to 3860 mAh / g, ten times that of commercial graphite anode) and extremely low electrochemical reaction potential, is regarded as an ideal negative electrode material for the new generation of high-performance energy storage batteries (such as lithium-sulfur batteries, lithium-air batteries and solid-state lithium metal batteries). However, the application of lithium metal in the field of negative electrodes faces a series of interrelated challenges, which mainly include the uncontrollable growth of lithium dendrites during charge and discharge cycles, the instability of the solid electrolyte interface film (SEI), and the huge volume changes of negative electrode materials during the charge and discharge process caused by this. These problems not only significantly reduce the energy conversion efficiency of the battery and shorten the battery life, but also bring safety risks that cannot be ignored. They have long been the key factors restricting the commercial application of lithium metal anodes.
[0003] Lithium aluminum alloy not only inherits the significant advantages of pure lithium metal negative electrode such as high specific capacity and low potential, but also exhibits unique physical and chemical properties, which makes it have broad application prospects in the field of lithium metal negative electrode modification. Lithium aluminum alloy exhibits excellent lithium affinity, which helps to promote the uniform deposition of lithium ions, thereby reducing the formation of lithium dendrites and improving the safety and cycle stability of the battery. Secondly, lithium aluminum alloys usually have high ionic conductivity, which helps to accelerate the diffusion process of lithium ions at the surface interface of the negative electrode and improve the charge and discharge rate and energy efficiency of the battery. In addition, lithium aluminum alloy also has high mechanical strength, which can enhance the interfacial bonding between the negative electrode and the solid electrolyte, improve the interface stability, and enhance the overall performance of the battery. In the future, with the continuous development of materials science and battery technology, lithium aluminum alloy materials are expected to play a more important role in the field of high-performance energy storage batteries.
[0004] However, for lithium-aluminum alloys, there are only intermetallic compounds and lithium and aluminum elements are not miscible, which faces some difficulties in the smelting preparation process. The melting points of lithium and aluminum are very different, and the two are not miscible in liquid, which makes it difficult to mix them evenly during the smelting process. This will cause uneven alloy composition and affect the overall performance of the alloy. Lithium and aluminum are prone to form intermetallic compounds during the smelting process. These compounds are usually hard and brittle, which will affect the subsequent processing performance of lithium-aluminum alloys, such as rolling and thinning.
[0005] Through the search of the prior art, the invention patent with application number CN201310220464.9 discloses a lithium aluminum alloy and its production method and use. However, the aluminum content in the lithium aluminum alloy prepared by this method is low, not exceeding 4.0wt%, and the microstructure of the lithium aluminum alloy is not disclosed. This method does not pay attention to the large-sized intermetallic compounds (such as Al 4 Li 9 , Al 2 Li 3 ), the presence of these large-sized intermetallic compounds has a significant impact on the quality of lithium aluminum alloys, especially for the preparation of ultra-thin lithium aluminum alloy strips below 50μm, they are a fatal factor. The invention patent application with application number CN202010036664.9 discloses a lithium aluminum alloy negative electrode material with controllable phase composition, a preparation method and an application. The focus of the method is to form a skeleton-like lithium aluminum alloy or a skeleton-like lithium aluminum alloy and a lithium aluminum alloy composed of metallic lithium filled in the skeleton. The lithium aluminum alloy contains a large amount of interconnected intermetallic compounds, which makes the overall material hard and brittle. Therefore, in terms of its own structure, this lithium aluminum alloy does not have the conditions for preparing high-quality ultra-thin lithium aluminum alloy strips.
[0006] It can be seen that in the prior art, it is difficult to solve the aluminum needle phenomenon (i.e., Al2O3) that occurs during the smelting and preparation process of lithium aluminum alloys (especially lithium aluminum alloys with an aluminum content higher than 3.0wt%). 4 Li 9 ,AlLi 2 、Al 2 Li 3 The phenomenon of intermetallic compound precipitation phase growth, etc., makes the lithium aluminum alloy unable to be rolled to a thickness below 50 μm, and the uneven segregation of aluminum elements will significantly affect the battery performance. In view of this, the present invention is proposed. Summary of the invention
[0007] In order to solve the above problems in the prior art, the present invention provides an ultra-thin lithium aluminum alloy strip and a preparation method and application thereof, which can effectively avoid the existence of holes when preparing high-end ultra-thin alloy strips of 50 μm and below, and fundamentally improve the quality of lithium aluminum alloy.
[0008] Based on this, the present invention has the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing an ultra-thin lithium aluminum alloy strip, comprising:
[0010] S1: stirring and melting high-purity metallic aluminum and high-purity metallic lithium to obtain a homogeneous liquid lithium-aluminum alloy; wherein the mass ratio of metallic lithium to metallic aluminum in the lithium-aluminum alloy is (9-999):1;
[0011] S2: Casting the liquid lithium aluminum alloy, rapidly cooling and solidifying it, and demolding it to obtain a lithium aluminum alloy rod; wherein the cooling rate is ≥100°C / s; and the diameter of the lithium aluminum alloy rod is ≤150mm;
[0012] S3: processing the lithium aluminum alloy rod to obtain an ultra-thin lithium aluminum alloy strip;
[0013] All the above operations were carried out under an inert gas atmosphere.
[0014] In the present invention, a non-equilibrium synthesis strategy is adopted, and the growth and precipitation of intermetallic compounds are suppressed by rapid solidification technology. At the same time, by controlling the diameter of the ingot, the difference in cooling rate inside and outside the entire ingot is reduced, and the consistency of the structure of all regions is ensured. This solves the problem of holes in the preparation of high-end ultra-thin alloy strips of 50μm and below, and fundamentally improves the quality of lithium-aluminum alloys.
[0015] Specifically, due to the fast cooling rate, a supersaturated solid solution of lithium aluminum alloy is obtained. At the same time, the high degree of supercooling increases the concentration of various intermetallic compounds (Al 4 Li 9 ,AlLi 2 、Al 2 Li 3 The number of nucleations (such as ) is increased, and the alloy solidifies rapidly to room temperature. The diffusion and migration rate of the aluminum element is greatly reduced, and the growth of the intermetallic compound precipitation phase is limited. Its size is controlled below 2μm~5μm. At the same time, the uniformity of element distribution in the lithium aluminum alloy can be greatly improved.
[0016] At the same time, during the casting process, the above-mentioned diameter of ≤150mm can further reduce the difference in cooling speed between the core and the outside of the lithium aluminum alloy, and prevent the cooling speed of the core lithium aluminum alloy from being much slower than that of the outside due to the excessive radial size, which slows down the heat transfer and causes the abnormal growth of the intermetallic compound precipitation phase in the core lithium aluminum alloy structure. Through vacuum pressure welding, the size of the lithium aluminum alloy rod changes from slender to thick and long, meeting the size required for high-efficiency wide strip extrusion.
[0017] In the present invention, the mass ratio of metallic lithium to metallic aluminum in the lithium aluminum alloy can be any ratio of 9:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1 and 999:1, or a ratio range with any two of the above ratios as endpoints.
[0018] Preferably, in S2, rapid cooling and solidification is achieved by oil-cooling the copper mold.
[0019] In the present invention, the characteristics of large thermal conductivity and fast heat dissipation of the oil-cooled copper mold are utilized, and the cooling speed of the lithium aluminum alloy casting is large during the casting process, thereby realizing rapid solidification of the lithium aluminum alloy.
[0020] Preferably, the diameter of the lithium aluminum alloy rod is 100-150 mm, for example, it can be 100 mm, 110 mm, 120 mm, 130 mm, 140 mm or 150 mm.
[0021] Preferably, the aluminum content in the lithium aluminum alloy is 0.1wt%~10.0wt%.
[0022] More preferably, the aluminum content in the lithium aluminum alloy is 3wt%~10.0wt%; for example, it can be 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10.0wt%.
[0023] Preferably, the smelting temperature in S1 is 530°C to 750°C, and more preferably 530°C to 700°C, which can ensure the quality of the lithium aluminum alloy strip while reducing the requirements for equipment. Specifically, it can be 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C.
[0024] The melting temperature used in the present invention is 530°C to 700°C, which is higher than the melting point of various intermetallic compounds precipitated in lithium aluminum alloy (lithium aluminum alloy with an aluminum content of 0.1wt.% to 10.0wt.%), such as Al 4 Li 9 Melting point 270℃, AlLi 2Melting point 355℃, Al 2 Li 3 Melting point 520°C. This melting temperature can ensure that the liquid lithium aluminum alloy is a uniform liquid phase, at which time the aluminum element is evenly distributed in the lithium metal and no intermetallic compounds exist.
[0025] Preferably, S3 comprises: subjecting the lithium aluminum alloy rod to roughening treatment, cold extrusion treatment and coating finish rolling treatment in sequence, so as to obtain the ultra-thin lithium aluminum alloy strip.
[0026] As a preferred embodiment of the present invention, the method for preparing the ultra-thin lithium aluminum alloy strip comprises:
[0027] S1: stirring and melting high-purity metallic aluminum and high-purity metallic lithium to obtain a homogeneous liquid lithium-aluminum alloy; wherein the mass ratio of metallic lithium to metallic aluminum in the lithium-aluminum alloy is (9-999):1;
[0028] S2: Casting the liquid lithium aluminum alloy, rapidly cooling and solidifying it through an oil-cooled copper mold, and demolding to obtain a lithium aluminum alloy rod; wherein the cooling rate is ≥100°C / s; and the diameter of the lithium aluminum alloy rod is ≤150mm;
[0029] S3: roughening the lithium aluminum alloy rod, vacuum pressurizing and welding 2 to 10 roughened samples to expand the diameter of the lithium aluminum alloy rod to more than 2 times; then cold extruding the lithium aluminum alloy rod with the expanded diameter to obtain a lithium aluminum alloy strip with a thickness of 100 μm to 1000 μm; finally, further coating and finishing rolling the cold extruded strip to obtain an ultra-thin lithium aluminum alloy strip with a thickness of 20 μm to 50 μm;
[0030] All the above operations were carried out under an inert gas atmosphere.
[0031] Compared with the prior art, the size of the intermetallic compound precipitated phase in the aluminum alloy (especially the high-content lithium aluminum alloy) is controlled in the present invention, the quality of the lithium aluminum alloy is greatly improved, and the preparation of ultra-thin strips below 50μm can be achieved. Secondly, the present invention uses oil-cooled copper molds as a cooling method, and combines small-diameter ingot casting with subsequent roughening and vacuum pressure welding. While meeting the extrusion requirements of wide-size strips, it not only ensures the consistency of the organization of the lithium aluminum alloy at various locations, but also does not reduce the efficiency of large-scale production.
[0032] In a second aspect, the present invention provides an ultra-thin lithium aluminum alloy strip, which is prepared by the preparation method of the ultra-thin lithium aluminum alloy strip.
[0033] In a third aspect, the present invention provides a negative electrode plate comprising the ultra-thin lithium aluminum alloy strip.
[0034] In a fourth aspect, the present invention provides a battery comprising the negative electrode plate.
[0035] The ultra-thin lithium aluminum alloy strip and its preparation method and application provided by the present invention control the size of the intermetallic compound to be below 2μm~5μm through process control, which is less than about one tenth of the target thickness (20μm~50μm) of the ultra-thin lithium aluminum alloy strip. In the process of initial thinning by cold extrusion and thinning by coating and finishing rolling of the lithium aluminum alloy, the small-sized metal compound always maintains good contact with the matrix and coordinated rheological properties with the matrix, and problems such as scraping the extrusion die during the extrusion process and generating holes during the rolling process will not occur. The technical difficulties in the processing of ultra-thin strips of lithium aluminum alloy (especially high-content lithium aluminum alloy) are solved, and the yield and quality of ultra-thin lithium aluminum alloy strips are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a surface photograph of the ultra-thin lithium aluminum alloy strip in Example 2 provided by the present invention.
[0038] Figure 2 middle, Figure 2 (a) is a scanning electron microscope image of the ultra-thin lithium aluminum alloy strip in Example 2 provided by the present invention, Figure 2 (b) is the EDS energy spectrum of the ultra-thin lithium aluminum alloy strip in Example 2 provided by the present invention.
[0039] Figure 3 This is a surface photograph of the ultra-thin lithium aluminum alloy strip in Example 3 provided by the present invention.
[0040] Figure 4 middle, Figure 4 (a) is a scanning electron microscope image of the ultra-thin lithium aluminum alloy strip in Example 3 provided by the present invention, Figure 4 (b) is the EDS energy spectrum of the ultra-thin lithium aluminum alloy strip in Example 3 provided by the present invention.
[0041] Figure 5 This is a surface photograph of the ultra-thin lithium aluminum alloy strip in Comparative Example 1 provided by the present invention.
[0042] Figure 6 middle, Figure 6 (a) is a scanning electron microscope image of the ultra-thin lithium aluminum alloy strip in Comparative Example 1 provided by the present invention, Figure 6(b) is the EDS energy spectrum of the ultra-thin lithium aluminum alloy strip in Comparative Example 1 provided by the present invention.
[0043] Figure 7 This is a surface photograph of the ultra-thin lithium aluminum alloy strip in Comparative Example 2 provided by the present invention.
[0044] Figure 8 middle, Figure 8 (a) is a scanning electron microscope image of the ultra-thin lithium aluminum alloy strip in Comparative Example 2 provided by the present invention, Figure 8 (b) is the EDS energy spectrum of the ultra-thin lithium aluminum alloy strip in Comparative Example 2 provided by the present invention.
[0045] Fig. 9 This is a surface photograph of the ultra-thin lithium aluminum alloy strip in Comparative Example 3 provided by the present invention.
[0046] Fig.10 middle, Fig.10 (a) is a scanning electron microscope image of the ultra-thin lithium aluminum alloy strip in Comparative Example 3 provided by the present invention, Fig.10 (b) is the EDS energy spectrum of the ultra-thin lithium aluminum alloy strip in Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0049] Example 1
[0050] This embodiment provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0051] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 3wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 590°C and a stirring melting time of 0.5h. After slag removal, it was cast and rapidly cooled in an oil-cooled copper mold at a cooling rate of ~120°C / s. The diameter of the cast alloy was 100mm. After the alloy was roughened, two identical alloys were vacuum pressurized and welded, followed by cold extrusion to obtain a 500μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning, and the final pass thickness was set to 30μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0052] Example 2
[0053] This embodiment provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0054] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 5wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 590℃ and a stirring melting time of 1h. After slag removal, it was cast and rapidly cooled in an oil-cooled copper mold at a cooling rate of ~120℃ / s. The diameter of the cast alloy was 100mm. After the alloy was roughened, two identical alloys were vacuum pressurized and welded, followed by cold extrusion to obtain a 500μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning, and the final pass thickness was set to 30μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0055] Among them, the surface photos of ultra-thin lithium aluminum alloy strips are shown in Figure 1 ; SEM images of ultra-thin lithium aluminum alloy strips are shown in Figure 2 (a), EDS spectrum is shown in Figure 2 (b).
[0056] Example 3
[0057] This embodiment provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0058] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 5wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 590℃ and a stirring melting time of 1h. After slag removal, it was cast and rapidly cooled in an oil-cooled copper mold at a cooling rate of ~120℃ / s. The diameter of the cast alloy was 100mm. After the alloy was roughened, two identical alloys were vacuum pressurized and welded, followed by cold extrusion to obtain a 1000μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning, and the final pass thickness was set to 50μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0059] Among them, the surface photos of ultra-thin lithium aluminum alloy strips are shown in Figure 3 ; SEM images of ultra-thin lithium aluminum alloy strips are shown in Figure 4 (a), EDS spectrum is shown in Figure 4 (b).
[0060] Example 4
[0061] This embodiment provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0062] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 10wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 690°C and a stirring melting time of 1h. After slag removal, it was cast and rapidly cooled in an oil-cooled copper mold at a cooling rate of ~120°C / s. The diameter of the cast alloy was 100mm. After the alloy was roughened, two identical alloys were vacuum pressurized and welded, followed by cold extrusion to obtain a 500μm thick lithium-aluminum alloy strip. The final pass thickness was set to 50μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0063] Example 5
[0064] This embodiment provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof is different from that of Embodiment 2 only in that the melting temperature is 750°C.
[0065] Example 6
[0066] This embodiment provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof is different from that of Embodiment 2 only in that the melting temperature is 500°C.
[0067] Comparative Example 1
[0068] This comparative example provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0069] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 5wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 590°C and a stirring melting time of 1h. After slag removal, the alloy was cast in a stainless steel mold and cooled naturally. The diameter of the cast alloy was 100mm. After the alloy was roughened, two identical alloys were vacuum pressurized and welded, followed by cold extrusion to obtain a 500μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning. The final pass thickness was set to 50μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0070] Among them, the surface photos of ultra-thin lithium aluminum alloy strips are shown in Figure 5 ; SEM images of ultra-thin lithium aluminum alloy strips are shown in Figure 6 (a), EDS spectrum is shown in Figure 6 (b).
[0071] Comparative Example 2
[0072] This comparative example provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0073] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 10wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 690°C and a stirring melting time of 1h. After slag removal, the alloy was cast in a stainless steel mold and cooled naturally. The diameter of the cast alloy was 100mm. After the alloy was roughened, two identical alloys were vacuum pressurized and welded, followed by cold extrusion to obtain a 500μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning, and the final pass thickness was set to 50μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0074] Among them, the surface photos of ultra-thin lithium aluminum alloy strips are shown in Figure 7 ; SEM images of ultra-thin lithium aluminum alloy strips are shown in Figure 8 (a), EDS spectrum is shown in Figure 8 (b).
[0075] Comparative Example 3
[0076] This comparative example provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0077] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 5wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 690℃ and a stirring melting time of 1h. After slag removal, an oil-cooled copper mold was used for casting and rapid cooling at a cooling rate of ~70℃ / s (the cooling rate of the ingot core was slower than that of the outside). The diameter of the cast alloy was 240mm, and then cold extrusion was performed to obtain a 500μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning, and the final pass thickness was set to 50μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0078] Among them, the surface photos of ultra-thin lithium aluminum alloy strips are shown in Fig. 9 ; SEM images of ultra-thin lithium aluminum alloy strips are shown in Fig.10 (a), EDS spectrum is shown in Fig.10 (b).
[0079] Comparative Example 4
[0080] This comparative example provides an ultra-thin lithium aluminum alloy strip, and the preparation method thereof comprises the following steps:
[0081] In an argon atmosphere in a glove box, a lithium-aluminum alloy with an aluminum content of 5wt.% was melted in a mechanically stirred crucible melting furnace at a melting temperature of 300°C and a stirring melting time of 2h. After slag removal, it was cast in a stainless steel mold and cooled naturally. The diameter of the cast alloy was 100mm, and then cold extrusion was performed to obtain a 500μm thick lithium-aluminum alloy strip. Finally, the coating finishing rolling method was used for rolling and thinning. The final pass thickness was set to 50μm to obtain an ultra-thin lithium-aluminum alloy strip.
[0082] Table 1 Thickness test results of lithium aluminum alloy strips of examples and comparative examples
[0083]
[0084] Table 2 Test results of aluminum element distribution uniformity of lithium aluminum alloy strips of embodiments and comparative examples
[0085]
[0086] The results in Tables 1 and 2 show that the thickness of the series of lithium aluminum alloy strips obtained by the preparation method of the present invention can reach the final set 30μm or 50μm, and the deviation of aluminum elements in various parts of the alloy is small. However, the thickness of the series of lithium aluminum alloy strips obtained by the conventional method cannot reach less than 50μm, and the deviation of aluminum elements in various parts of the alloy is large.
[0087] From the surface photos and scanning electron microscope images of the lithium aluminum alloy strips in each embodiment and comparative example ( Figure 1 to Figure 10 ) It can be seen that the series of lithium aluminum alloy strips prepared by the preparation method of the present invention have a smooth surface without defects, and the size of the intermetallic compounds in the microstructure is very small (<5μm). However, the series of lithium aluminum alloy strips prepared by the conventional method have an uneven surface, a large number of holes and particles, and the size of the intermetallic compounds in the microstructure is very large (>50μm).
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an ultra-thin lithium aluminum alloy strip, characterized in that: include: S1: stirring and melting high-purity metallic aluminum and high-purity metallic lithium to obtain a homogeneous liquid lithium-aluminum alloy; wherein the mass ratio of metallic lithium to metallic aluminum in the lithium-aluminum alloy is (9-999):1; S2: Casting the liquid lithium aluminum alloy, rapidly cooling and solidifying it, and demolding it to obtain a lithium aluminum alloy rod; wherein the cooling rate is ≥100°C / s; and the diameter of the lithium aluminum alloy rod is ≤150mm; S3: roughening the lithium aluminum alloy rod, vacuum pressurizing and welding 2 to 10 roughened samples to expand the diameter of the lithium aluminum alloy rod to more than 2 times; then cold extruding the lithium aluminum alloy rod with the expanded diameter to obtain a lithium aluminum alloy strip with a thickness of 100 μm to 1000 μm; finally, further coating and finishing rolling the cold extruded strip to obtain an ultra-thin lithium aluminum alloy strip with a thickness of 20 μm to 50 μm; All the above operations were carried out under an inert gas atmosphere.
2. The method for preparing the ultra-thin lithium aluminum alloy strip according to claim 1, characterized in that: In S2, rapid cooling and solidification are achieved by oil-cooling the copper mold.
3. The method for preparing the ultra-thin lithium aluminum alloy strip according to claim 1, characterized in that: The diameter of the lithium aluminum alloy rod is 100-150 mm.
4. The method for preparing the ultra-thin lithium aluminum alloy strip according to claim 1, characterized in that: The aluminum content in lithium aluminum alloy is 3wt%~10.0wt%.
5. The method for preparing the ultra-thin lithium aluminum alloy strip according to claim 1, characterized in that: The smelting temperature in S1 is 530°C to 750°C.
6. The method for preparing the ultra-thin lithium aluminum alloy strip according to claim 1, characterized in that: S3 comprises: subjecting the lithium aluminum alloy rod to roughening treatment, cold extrusion treatment and coating finish rolling treatment in sequence, so as to obtain the ultra-thin lithium aluminum alloy strip.
7. An ultra-thin lithium aluminum alloy strip, characterized in that: The ultra-thin lithium aluminum alloy strip is prepared by the preparation method of any one of claims 1 to 6.
8. A negative electrode plate, characterized in that: It contains the ultra-thin lithium aluminum alloy strip as described in claim 7.
9. A battery, characterized in that: It contains the negative electrode sheet according to claim 8.
Citation Information
Patent Citations
Lithium-aluminum alloys, their production methods and applications
CN103290293B
Object-phase component controllable lithium aluminum alloy negative electrode material and preparation method and application
CN111187948A
Lithium alloy negative electrode material, preparation method thereof and lithium ion battery
CN116936790A